A Study of China's Foreign Aid An Asian Perspective - Shimomura, Y.; Ohashi, H.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This book provides a new perspective of China's controversial foreign aid strategy. The chapters offer a thorough examination of data to show how China has created knowledge in its long experiences of aid and how this accumulated knowledge could contribute to other developing countries. The book also examines China's aid philosophy and strategy through an Asian perspective, instead of the Western perspective that is postulated in existing academic literature. This is important as China shares a number of common features with other Asian donors, including India and Japan. Finally, the book explores how to utilize the potential effect of this rising major donor for worldwide development and poverty reduction.
Keywords: Development economics; Regional economics; Spatial economics; Economic development; Political economy; International economics; Economic growth; Development Economics; Regional/Spatial Science; Development Studies; International Political Economy; International Economics; Economic Growth